2022
DOI: 10.1002/alz.12534
|View full text |Cite
|
Sign up to set email alerts
|

Identifying differential regulatory control of APOE ɛ4 on African versus European haplotypes as potential therapeutic targets

Abstract: We previously demonstrated that in Alzheimer's disease (AD) patients, European apolipoprotein E (APOE) ε4 carriers express significantly more APOE ε4 in their brains than African AD carriers. We examined single nucleotide polymorphisms near APOE with significant frequency differences between African and European/Japanese APOE ε4 haplotypes that could contribute to this difference in expression through regulation. Two enhancer massively parallel reporter assay (MPRA) approaches were performed, supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…S4). Additionally, several independent studies have also demonstrated chromosomal interactions within this APOE locus [43,44]. Our findings suggest that these four APOE locus genes are located within a single TAD, creating a 3D genomic environment that facilitates their coregulation.…”
Section: D Genome Structure Of the Apoe Locussupporting
confidence: 59%
See 1 more Smart Citation
“…S4). Additionally, several independent studies have also demonstrated chromosomal interactions within this APOE locus [43,44]. Our findings suggest that these four APOE locus genes are located within a single TAD, creating a 3D genomic environment that facilitates their coregulation.…”
Section: D Genome Structure Of the Apoe Locussupporting
confidence: 59%
“…Recently, research in AD has applied this concept [75,76]. Based on evidence from chromosome conformation capture [42][43][44], it is likely that multiple genes within the APOE locus are coregulated within the same TAD. Therefore, TADs are well-suited to study the mechanisms of of multiple genes within APOE locus.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the increased APOE4 expression previously reported in ELA APOE4 carriers 11 may be partly due to differences in chromatin remodeling at the promoter of APOE4 between ancestries. We have also shown using Capture Chromatin Conformation analysis and massively parallel reporter assays that specific DNA sequence differences in areas physically interacting with the APOE promoter have functional effects in microglia and astrocytes, with greater expression occurring in ELA sequence variants than ALA 60 . Thus, given the long-time span of AD, it appears that multiple mechanisms affecting APOE4 gene expression in astrocytes may be activated at different times in life or by stress and could affect the differences in AD risk seen between ancestral homozygous APOE4 carriers.…”
Section: Discussionmentioning
confidence: 90%
“…These results suggest that the increased APOE ε4 expression previously reported in ELA APOE ε4 carriers 11 may be partially due to differences in chromatin remodeling at the promoter of APOE ε4 between ancestries. We have also shown using chromatin conformation capture analysis and massively parallel reporter assays that specific DNA sequence differences in areas physically interacting with the APOE promoter have functional effects in microglia and astrocytes, with greater expression occurring in ELA sequence variants than ALA. 59 Thus, multiple mechanisms affecting APOE ε4 gene expression in astrocytes may be activated at different times in life or by stress and could affect the differences in AD risk seen between ancestral homozygous APOE ε4 carriers. This emphasizes that the APOE loci is under a complex regulatory environment that involves cell typespecific processes and strengthens the primary functional role of APOE in astrocytes.…”
Section: Discussionmentioning
confidence: 99%